Hubungan Multi Paritas dengan Tingkat Kejadian Kanker Serviks di RSUD Dr Moewardi - Siswanto, Totok; Yuliantara, Eric Edwin; Wijayanti, Lilik (Nexus Kedokteran Klinik, 2014)
Background: Cervical cancer is one of the most common cancer found in women and ranks second all cancers in women in the world. Multi parity thought to be one of the risk factors for cervical cancer. Hormonal and anatomical changes that occur in multi parity may increase the risk of cervical cancer by a variety of mechanisms. The purpose of this study was to determine the incidence rates of cervical cancer are associated with multi parity status. Methods: The type of research is an case-control. The samples in this study were patients with cervical cancer and other gynecological diseases with a total sample of 60 people. Measuring instrument used was a questionnaire, and then performed the data analysis with multiple logistic regression analysis. Result: Found a statistically significant association between the multi-parity status with the incidence of cervical cancer. People with multi-parity status have an increased risk for cervical cancer was 8.986 times greater than women with non-multi-parity status (p = 0.003, OR = 8.986). Conclusion: Based on research ofÂ  woman with multi parity status will have the risk of having cervical cancer by 8,986 times compared to women with non-multi-parity status. Key Words: multi parity, cervical cancerÂ